1978
DOI: 10.1073/pnas.75.5.2215
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic receptor that specifically binds oligosaccharides containing fucosyl α1→3 N -acetylglucosamine linkages

Abstract: Evidence is presented suggesting that hepatocytes contain a receptor that binds glycoproteins specifically through fucose in al-..3 linkage to N-acetylglucosamine. Human After the initial observations of Ashwell and coworkers (1, 2) that mammalian hepatocytes contain a protein that specifically binds asialoglycoproteins through exposed galactose residues, several other animal binding proteins were reported. A (3-galactoside binding protein has been described from calf heart and lung (3), chick embryo thigh m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1
1

Year Published

1979
1979
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(66 citation statements)
references
References 22 publications
5
59
1
1
Order By: Relevance
“…Recently a fucose-binding from the present study, those for rat liver, kidney and brain from [lo], those for human erythrocytes from [12]. The hatched areas in erythrocytes refer to the portion found as poly(glycosy1)peptides [12] protein specific for the sequence Gal(/31+4)[Fuc-(a1 -+ 3)IGlcNAc has been described [5]. The amount of fucose was found to be very low in plasma glycoproteins and it appeared to be bound by other types of linkages, since almost no 3 or 3,4-disubstituted N-acetylglucosamine residues were found to be present.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a fucose-binding from the present study, those for rat liver, kidney and brain from [lo], those for human erythrocytes from [12]. The hatched areas in erythrocytes refer to the portion found as poly(glycosy1)peptides [12] protein specific for the sequence Gal(/31+4)[Fuc-(a1 -+ 3)IGlcNAc has been described [5]. The amount of fucose was found to be very low in plasma glycoproteins and it appeared to be bound by other types of linkages, since almost no 3 or 3,4-disubstituted N-acetylglucosamine residues were found to be present.…”
Section: Discussionmentioning
confidence: 99%
“…Fucose has been shown to be a part of antigenic determinants, including the so called X-antigen (34), and may be also be part of the receptor for the macrophage migration inhibitory factor (35) . A specific hepatic uptake system for the a l ---+ 3 linked fucose has also been described (36) . One of the WGARLots cell lines has been shown to differ from the parent cells with respect to cell adhesion and metastasis (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Cells (5 x 105) in 0.1 ml were layered over oil (4 parts silicon oil plus I part mineral oil) in Microfuge (Beckman) tubes. The interaction of ligand with cells was terminated by sedimentation for 30 (6). Previous work has shown that the rate at which -glucuronidase is cleared from plasma is sharply decreased by the simultaneous administration of mannose-or Nacetylglucosamine-terminated glycoproteins (6,8).…”
Section: Methodsmentioning
confidence: 99%